Racism and Justice : The Case for Affirmative Action - Ezorsky, Gertrude, 1926- (Book collections on Project MUSE., 1991)
Affirmative action: does it really counteract racism? Is it morally justifiable? In her timely and tough-minded book, Gertrude Ezorsky addresses these central issues in the ongoing controversy surrounding affirmative action, and comes up with some convincing answers. Ezorsky begins by examining the effectiveness of affirmative action as a remedy for institutional racism in the workplace. She analyzes the ways in which common practices-selection of employees based on personal connections, qualification, and seniority standards-perpetuate the injurious effect of past racial discrimination, and she assesses the rationale for such affirmative action measures as objective job-related testing, numerical goals, and preferential treatment for basically qualified blacks. To illuminate the social reality in which affirmative action takes place, she draws on recent work by social scientists and legal scholars. Turning to the moral issues, Ezorsky posits two basic justifications for affirmative action: first, looking backward-to provide deserved compensation for past racial injustice that was sanctioned, practiced, and encouraged by our government; second, looking forward-to promote racial desegregation in the American workplace. Unlike some supporters of affirmative action, she does not deny that preferential treatment may place an unfair burden on white males. Indeed, she suggests specific practical measures for spreading that burden more equitably. Clear-headed, well-reasoned, and persuasive, this book will be read eagerly by everyone from students to legislators, by anyone concerned with racial justice in America.